Over‐promotion and caution in abstracts of preprints during the COVID ‐19 crisis - Bordignon, Frédérique; Ermakova, Liana; Noël, Marianne (Learned Publishing, 2021)
Abstract The abstract is known to be a promotional genre where researchers tend to exaggerate the benefit of their research and use a promotional discourse to catch the reader's attention. The COVID‐19 pandemic has prompted intensive research and has changed traditional publishing with the massive adoption of preprints by researchers. Our aim is to investigate whether the crisis and the ensuing scientific and economic competition have changed the lexical content of abstracts. We propose a comparative study of abstracts associated with preprints issued in response to the pandemic relative to abstracts produced during the closest pre‐pandemic period. We show that with the increase (on average and in percentage) of positive words (especially effective) and the slight decrease of negative words, there is a strong increase in hedge words (the most frequent of which are the modal verbs can and may). Hedge words counterbalance the excessive use of positive words and thus invite the readers, who go probably beyond the ‘usual’ audience, to be cautious with the obtained results. The abstracts of preprints urgently produced in response to the COVID‐19 crisis stand between uncertainty and over‐promotion, illustrating the balance that authors have to achieve between promoting their results and appealing for caution.